Impact of rapid molecular testing on diagnosis, treatment and management of community-acquired pneumonia in Norway: a pragmatic randomised controlled trial (CAPNOR) - Sondre Serigstad; Christian Ritz; Daniel Faurholt-Jepsen; Dagfinn Markussen; Marit H. Ebbesen; Øyvind Kommedal; Rune O. Bjørneklett; Lars Heggelund; Tristan W. Clark; Cornelis H. van Werkhoven; Siri T. Knoop; Elling Ulvestad; et al. (Trials, 2022)
Abstract Background Community-acquired pneumonia (CAP) causes a large burden of disease. Due to difficulties in obtaining representative respiratory samples and insensitive standard microbiological methods, the microbiological aetiology of CAP is difficult to ascertain. With a few exceptions, standard-of-care diagnostics are too slow to influence initial decisions on antimicrobial therapy. The management of CAP is therefore largely based on empirical treatment guidelines. Empiric antimicrobial therapy is often initiated in the primary care setting, affecting diagnostic tests based on conventional bacterial culture in hospitalized patients. Implementing rapid molecular testing may improve both the proportion of positive tests and the time it takes to obtain test results. Both measures are important for initiation of pathogen-targeted antibiotics, involving rapid de-escalation or escalation of treatment, which may improve antimicrobial stewardship and potentially patient outcome. Methods Patients presenting to the emergency department of Haukeland University Hospital (HUH) in Bergen, Norway, will be screened for inclusion into a pragmatic randomised controlled trial (RCT). Eligible patients with a suspicion of CAP will be included and randomised to receive either standard-of-care methods (standard microbiological testing) or standard-of-care methods in addition to testing by the rapid and comprehensive real-time multiplex PCR panel, the BioFire® FilmArray® Pneumonia Panel plus (FAP plus) (bioMérieux S.A., Marcy-l’Etoile, France). The results of the FAP plus will be communicated directly to the treating staff within ~2 h of sampling. Discussion We will examine if rapid use of FAP plus panel in hospitalized patients with suspected CAP can improve both the time to and the proportion of patients receiving pathogen-directed treatment, thereby shortening the exposure to unnecessary antibiotics and the length of hospital admission, compared to the standard-of-care arm. The pragmatic design together with broad inclusion criteria and a straightforward intervention could make our results generalizable to other similar centres. Trial registration ClinicalTrials.gov NCT04660084 . Registered on December 9, 2020